2009
DOI: 10.1155/2009/928306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Study of Two Tooth Bleaching Protocols with 6% Hydrogen Peroxide

Abstract: Objective. The objective was to compare the clinical efficacy of two different tooth bleaching protocols after 1 and 2 weeks of treatment with an over-the-counter paint-on gel containing 6% hydrogen peroxide. Material and methods. Sixteen volunteer patients (minimum shade A2 or darker on maxillary teeth) were selected to participate in this randomized, single-blind (examiner-blinded), single-center, 2-group clinical trial using a divided mouth model. The product was applied in our clinic to one hemi-arch (Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…Today's bleaching systems are the result of efforts to increase patient benefits in terms of better bleaching efficacy and ease of use [ 20 ]. Various light sources are being used in dental clinics, as they are known to reduce the total treatment time; however, the bleaching effects caused by such light sources remain unclear [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Today's bleaching systems are the result of efforts to increase patient benefits in terms of better bleaching efficacy and ease of use [ 20 ]. Various light sources are being used in dental clinics, as they are known to reduce the total treatment time; however, the bleaching effects caused by such light sources remain unclear [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…At-home whitening should be supervised by a dental professional and consists of the application of different concentrations of a peroxide gel (carbamide or hydrogen) to the teeth with the aid of personalized molds [ 9 ]. A number of publications have attested to the efficacy and biological safety of the at-home method [ 2 , 10 , 16 ]. Since the first proposal for home tooth whitening by Haywood and Heymann [ 9 ], both in vitro and in situ studies have demonstrated that whitening does not harm dental tissues and allows surprising esthetic results when properly employed [ 1 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Complex molecules of organic pigments in the tissues are broken down into simpler hydrophilic molecules through an oxidation-reduction reaction by the action of perhydroxyl ions originating from the degradation of H 2 O 2 [ 1 ]. These simpler molecules are easily removed from the dental tissue when in contact with water, thereby providing the desired whitening effect [ 5 , 6 , 16 20 ]. This is the action mechanism of peroxide in both the whitening process performed in the dentist’s office and the self-administered method performed in the comfort of the patient’s own home [ 1 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased salivation occurs frequently in patients while wearing a splint, which is a common occurrence due to pH change in the mouth. 1,3,5,[8][9][10][11][12][13][14][15][16][17] Zekonis et al examined colour change, recurrence of discoloration and tooth sensitivity after performing two different dental bleaching techniques in the same patient. In-office bleaching technique with 35% hydrogen peroxide gel was used on one half of the upper jaw of the subjects, while at-home night-guard bleaching technique with 10% carbamide peroxide gel was applied on the other half.…”
Section: 4-10mentioning
confidence: 99%
“…These self-applied bleaching treatments are administered without the consultation and supervision of a dentist. 1,[4][5][6][7][8][9] In-office dental bleaching techniques use high concentrations of hydrogen or carbamide peroxide gel. The gel is placed on a specific surface of the tooth and then activated chemically or by various light and heat sources.…”
Section: Introductionmentioning
confidence: 99%